Good economics for hard times - Banerjee, Abhijit V., 1961-; Duflo, Esther, 1972- (New Delhi : Juggernaut, 2021)
"Figuring out how to deal with today's critical economic problems is perhaps the great challenge of our time. Much greater than space travel or perhaps even the next revolutionary medical breakthrough, what is at stake is the whole idea of the good life as we have known it. Immigration and inequality, globalization and technological disruption, slowing growth and accelerating climate change--these are sources of great anxiety across the world ... The resources to address these challenges are there--what we lack are ideas that will help us jump the wall of disagreement and distrust that divides us. If we succeed, history will remember our era with gratitude; if we fail, the potential losses are incalculable. In this ... book, renowned MIT economists Abhijit V. Banerjee and Esther Duflo take on this challenge"--Publisher's description.
MEGA : make economics great again -- From the mouth of the shark -- The pains from trade -- Likes, wants, and needs -- The end of growth? -- In hot water -- Player piano -- Legit.gov -- Cash and care -- Conclusion : good and bad economics.
Includes bibliographical references (pages 327-383) and index.
BIGD
Keywords: Economics; Economic history -- 1990-; Globalization; BUSINESS & ECONOMICS / Economics / Macroeconomics; POLITICAL SCIENCE / Public Policy / Economic Policy; SOCIAL SCIENCE / Social Classes & Economic Disparity